2015
DOI: 10.7314/apjcp.2014.15.24.10557
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-associated Targeting Pathways of Natural Products during Cancer Treatment

Abstract: It is well known that conventional chemotherapy and radiation therapy can result in toxicity to both normal cells and tumor cells, which causes limitations in the application of these therapeutic strategies for cancer control. Novel and effective therapeutic strategies for cancers with no or low toxicity for normal cells are a high priority. Therefore, natural products with anticancer activity have gained more and more attention due to their favorable safety and efficacy profiles. Pre-clinical and clinical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 80 publications
0
45
0
Order By: Relevance
“…On the other hand, autophagy may play an oncogenic role by maintaining tumor cell survival and preventing apoptotic cell death after anticancer treatment. Recently, several studies demonstrated that natural compounds with anticancer abilities could induce autophagy in different types of tumors (20)(21)(22). However, the precise role of autophagy (tumor suppressor or promoter) involved in the mechanism of natural compound-induced cancer cell death needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, autophagy may play an oncogenic role by maintaining tumor cell survival and preventing apoptotic cell death after anticancer treatment. Recently, several studies demonstrated that natural compounds with anticancer abilities could induce autophagy in different types of tumors (20)(21)(22). However, the precise role of autophagy (tumor suppressor or promoter) involved in the mechanism of natural compound-induced cancer cell death needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date various pathways underlying the programmed cell death include apoptosis, autophagy, and necroptosis, as reviewed elsewhere [18-23]. While numerous reviews focused on the apoptotic pathways, extrinsic and intrinsic alike, we concentrate our efforts on the latest developments regarding autophagy and necroptosis induced by natural compounds in tumor cells [24-29]. Apoptosis is the most often occurred mechanism of tumor cell death induced upon chemotherapeutic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, its function as an active cell death mechanism remains controversial [1]. Actually, most reported autophagy induced by natural products was prosurvival [6, 7]. Regulated necrosis is morphologically characterized by cytoplasmic granulation, organelle and/or cellular swelling resulting from cellular leakage [8].…”
Section: Introductionmentioning
confidence: 99%